2023
DOI: 10.1038/s41467-023-37067-x
|View full text |Cite
|
Sign up to set email alerts
|

Seismic evidence for a 1000 km mantle discontinuity under the Pacific

Abstract: Seismic discontinuities in the mantle are indicators of its thermo-chemical state and offer clues to its dynamics. Ray-based seismic methods, though limited by the approximations made, have mapped mantle transition zone discontinuities in detail, but have yet to offer definitive conclusions on the presence and nature of mid-mantle discontinuities. Here, we show how to use a wave-equation-based imaging method, reverse-time migration of precursors to surface-reflected seismic body waves, to uncover both mantle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…(2019). The mid‐mantle reflectors or scatters may be caused by other mechanisms, for example, the post‐stishovite phase transition in pure or aluminous‐hydrous silica (Umemoto et al., 2016; Wang et al., 2020) in stagnant subducted slabs (Zhang et al., 2023). Recently, Ko et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019). The mid‐mantle reflectors or scatters may be caused by other mechanisms, for example, the post‐stishovite phase transition in pure or aluminous‐hydrous silica (Umemoto et al., 2016; Wang et al., 2020) in stagnant subducted slabs (Zhang et al., 2023). Recently, Ko et al.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the tetragonal to cubic transition in CaPv cannot explain the seismic wave speed anomalies in the lower mantle, contrary to the claim of Thomson et al (2019). The mid-mantle reflectors or scatters may be caused by other mechanisms, for example, the post-stishovite phase transition in pure or aluminous-hydrous silica (Umemoto et al, 2016;Wang et al, 2020) in stagnant subducted slabs (Zhang et al, 2023). Recently, Ko et al suggested that the dissolution behavior of CaPv in bridgmanite can lead to its disappearance as a separate phase at depths greater than 1,800 km, a new insight into the deep mantle mineralogy (Ko et al, 2022).…”
Section: Geophysical Research Lettersmentioning
confidence: 88%
“…More sophisticated solutions should properly consider the sensitivity kernel of SS precursors using migration or full waveform modeling (Koroni et al., 2017). The proposed method can offer a useful preconditioning tool to improve the quality of SS precursors for the pre‐stack migration imaging as has been investigated in a recent study (Z. Zhang et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method can offer a useful preconditioning tool to improve the quality of SS precursors for the prestack migration imaging as has been investigated in a recent study (Z. Zhang et al, 2023).…”
Section: Reliability Of the Mtz Imagingmentioning
confidence: 99%
“…Intricate plume structures comprising ponding zones (Nolet et al 2006;Wamba et al 2021Wamba et al , 2023 and branching networks have been imaged, e.g., in the Indian Ocean beneath La Réunion (Tsekhmistrenko et al 2021;Wamba et al 2023) and in the Antarctic Rift System beneath Marie Byrd Land (e.g., Hansen et al 2014). Beneath the Central Pacific around Hawaii, seismically slow material may have accumulated in the mid-mantle (Shen et al 2003;Yu et al 2018;Zhang et al 2023).…”
mentioning
confidence: 99%